Feeding the Future with the Past: Incorporating Local Ecological Knowledge in River Restoration - Ewelina Szałkiewicz; Joanna Sucholas; Mateusz Grygoruk (Resources, 2020)
Despite many years of experience in the river restoration field, which has become one of the most promising areas of water resources management, significant challenges and problems remain. These include the scope and scale of restoration measures, developing the reference model, assessment of restoration success, and the engagement of local stakeholders. Progress in addressing these challenges to river restoration could be achieved by changes in current approaches through the appreciation and integration of local communities and their local ecological knowledge (LEK). The results of discussion on ecological restoration indicate that ecological knowledge, which combines the interests of local communities and the environment, could be used in restoration projects. However, in the case of river restoration, this type of knowledge is systematically overlooked. In our paper, we discuss common river restoration problems and supportive elements that may be found in LEK. We conclude that the local stakeholders’ involvement and strong establishment of their position in the river restoration processes should be reconsidered. We believe that the application of LEK has large potential for improving water resources management and restoration of aquatic ecosystems and remains a key factor in a successful future of river restoration.